Investigating the relationships between motor skills, cognitive status, and area deprivation index in Arizona: a pilot study - Hooten, Madeline; Ortega, Marcus; Oyeyemi, Adewale; Yu, Fang; Ofori, Edward (Frontiers in Public Health, 2024)
Previous studies highlight the negative impact of adverse socioeconomic conditions throughout life on motor skills and cognitive health. Factors such as cognitive activity, physical activity, lifestyle, and socioeconomic position significantly affect general health status and brain health. This pilot study investigates the relationships among the Area Deprivation Index (ADI)-a measure of neighborhood-level socioeconomic deprivation, brain structure (cortical volume and thickness), and cognitive status in adults in Arizona. Identifying measures sensitive to ADI could elucidate mechanisms driving cognitive decline.METHODS: The study included 22 adults(mean age = 56.2 ± 15.2) in Arizona, residing in the area for over 10 years(mean = 42.7 ± 15.8). We assessed specific cognitive domains using the NeuroTrax™ cognitive screening test, which evaluates memory, executive function, visualspatial processing, attention, information processing speed, and motor function. We also measured cortical thickness and volume in 10 cortical regions using FreeSurfer 7.2. Linear regression tests were conducted to examine the relationships between ADI metrics, cognitive status, and brain health measures. RESULTS:Results indicated a significant inverse relationship between ADI metrics and memory scores, explaining 25% of the variance. Both national and state ADI metrics negatively correlated with motor skills and global cognition (r's< -0.40, p's<0.05). In contrast, ADI metrics generally positively correlated with motor-related volumetric and cortical thickness measures (r's>0.40, p's<0.05).CONCLUSION: The findings suggest that neighborhood-level social deprivation might influence current memory and motor status primarily through motor brain health. This indicates that motor function markers could provide valuable insights into the impact of social determinants on health.